1996
DOI: 10.1021/jp9526511
|View full text |Cite
|
Sign up to set email alerts
|

Silylation To Improve Incorporation of Zeolites in Polyimide Films

Abstract: The silylation of borosilicate with APTS ((γ-aminopropyl)triethoxysilane) is studied as a tool to improve zeolite incorporation in PI (polyimide) films. Among other experimental parameters, a quantification of the zeolite outer surface silanols is performed in order to determine the most appropriate silylation conditions. Xylene sorptions, NMR (nuclear magnetic resonance) spectroscopy, and measurements of the specific surface of the zeolites were performed to characterize the silylation. Finally, the silylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 37 publications
0
49
0
2
Order By: Relevance
“…A silane coupling agent generally can enhance the adhesion between polymer matrix and inorganic filler [12]. Therefore, in this study, the effects of chemical modification on zeolite surface with 3-aminopropyltriethoxysilane (Dynasylan ® Ameo) for fabricated PES-zeolite mixed matrix hollow fiber membrane were examined.…”
Section: Characterization Of Polyethersulfone Mixed Matrix Hollow Fibmentioning
confidence: 99%
“…A silane coupling agent generally can enhance the adhesion between polymer matrix and inorganic filler [12]. Therefore, in this study, the effects of chemical modification on zeolite surface with 3-aminopropyltriethoxysilane (Dynasylan ® Ameo) for fabricated PES-zeolite mixed matrix hollow fiber membrane were examined.…”
Section: Characterization Of Polyethersulfone Mixed Matrix Hollow Fibmentioning
confidence: 99%
“…Thus, the formed MMMs showed no significant improvement in selectivity due to the bypassing of the gas in the gap around the fillers. However, subsequent works showed that the use of a silane coupling agent, APTS, improved the adhesion properties between the polymer and fillers, leading to improved properties [111]. Vu et al [98] also found initially that by using CMS at various loadings in Ultem and Matrimid 5218, poor polymer-sieve contact and aggregation were observed.…”
Section: Interfacial Defects In MMMmentioning
confidence: 99%
“…However there is scope for further improvement of the performances of ISG hybrid membranes through modification of the polymer matrix. Chemical modification techniques have been successfully applied to MMMs containing inorganic particles to improve the interaction between the polymer and inorganic phases of the membranes for gas separations [18,19] and OSN [13,20].…”
Section: Introductionmentioning
confidence: 99%